Effects of an Adolescent Obesity Management Educational Program on Middle and High School Teachers in South Korea - Hae Young Min, PhD, RN; Shin-Jeong Kim, PhD, RN; Haeryun Cho, PhD, RN (Elsevier, 2017)
Purpose: This study aimed to examine the effects of an adolescent obesity management educational program (AOMEP) on middle and high school teachers. Methods: A quasiexperimental, pretest post-test design was performed to test primary variables, including adolescent obesity management knowledge, attitudes, perceived behavioral control, and behavioral intention based on the concepts presented in the Theory of Planned Behavior. Results: A total of 61 teachers participated. The experimental group (n = 30) received 15 hours of AOMEP, whereas the control group (n = 31) did not receive any. The experimental group showed significant improvement in knowledge (t = 2.53, d = .65, p = .014) and attitude (t = 2.77, d = .71, p = .008) toward adolescent obesity management compared to the control group. However, there were no significant differences in perceived behavioral control or behavioral intention between the groups. Conclusions: AOMEP may be utilized as an effective obesity management program for adolescent students in schools.